Investor behavior in times of conflict: A natural experiment on the interplay of geopolitical risk and defense stocks - Klein, Tony (Journal of economic behavior & organization, 2024)
We examine the connectedness of aerospace and defense companies and their relation to measures of geopolitical risk. With hierarchical clustering, we find stable and localized company clusters. Increasing geopolitical risk leaves these clusters intact but strengthens inter-cluster connectedness. Focusing on intraday data, we find that for most companies, instantaneous news arrival in form of jumps impacts realized volatility significantly. Further, we show that different measures of geopolitical uncertainty (GPR and COVOL) have differing impact on short-term predictions of intraday volatility, underlying the importance to distinguish between different sources of uncertainty. We provide evidence that investors react instantaneously to increases in geopolitical risk with some persistence of these shocks. The COVOL index holds significant informational content for short- and medium-term predictions of realized volatility of global aerospace and defense companies. •Aerospace and defense companies form localized clusters.•Increasing geopolitical risk increases the intercluster connectedness.•Different measures of geopolitical risks (GPR and COVOL) affect realized volatility predictions.•Instantaneous news arrival in form of volatility jumps are causally related to changes in geopolitical risk.•We provide evidence that investors react instantaneously to increases in geopolitical risk.